PEMILIHAN JENIS AIRFOIL MOHINDER UNNES MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS - Al-Janan, Dony; Gusda, Yoga (Jurnal Rekayasa Mesin, 2024)
An UAV (Unmanned Aerial Vehicle) is an aircraft without an onboard pilot that has several functions. Mohinder is one of the fixed-wing UAVs used for mapping and monitoring areas. Currently, the Mohinder UNNES is adopted from other UAVs by reduced-scale X-UAV Talon. There are differences between dimensions and cruising speed among Mohinder and X-UAV Talon (Mohinder adaptation). The purpose of this study is to select the suitable Mohinder’s airfoil using XFLR 5 simulation using multi-criteria decision particularly the AHP (Analytical Hierarchy Process). AHP can break down the choosing into a hierarchy, compare each factor's importance, and use math to figure out the best choice based on the preferences. The selection criteria are Max Camber, Thickness α stall, Max L/Dmax, CLmax, and CL0, so then the basic airfoil shapes are AH 79-100 B, S1223 RTL, FX 63-120, dan EPPLER 395. Mohinder airfoil will be selected based on aerodynamic performance at Reynold number 200.000. The simulation results showed the AH 79-100 B airfoil has higher L/Dmax and Cl at angle of attack (AOT) -10° to 20° compared to airfoil MH-32 (Mohinder current airfoil)